Animation for visualization of some algebraic concepts - Mohammed Ismail, Abdulwahid (2003)
Presenting the sciences and teaching the courses in an interactive way is one of the most attractive aspects of the web and educational technology. Many mathematical softwares demonstrate how these technologies make advance topics more accessible and complex mathematical concepts more understandable. The common problems in mathematics teaching process; is the difficulties, undergraduate students encounter in understanding math concepts, theories and problem solving. These problems can be overcome through using creativity in developing math teaching tools and styles. The objective of this project is to use macromedia Flash to make many confusing and complex math concepts simple, visualized and interesting and also to develop a part of a package of animated and visualized mathematical courses. Flash ability and flexibility are the features of this tool which help the designer to develop demonstrating of algebra concepts in a virtual environment. This research will use Macromedia Flash for developing a visualized package of algebra course (Introduction to Algebra (MTK 3001).